Discovery-learning-based Module Development Enriched with Sambas Folklore on the Sub Material Classification of Living Things - Fatimah, Siti; Candramila, Wolly; Tenriawaru, Andi Besse (Jurnal Mangifera Edu, 2023)
This study aims to develop a module as teaching materials on the Sub Material Living Things Classification of living things sub-material with a discovery learning approach combined with folklore and determine students' responses to these teaching materials. This study uses the first three stages of the Thiagarajan 4D model development method: define, design, develop, and disseminate. The research instruments used were validation sheets and questionnaires. The sample in this study was class X high school students consisting of 15 people. The five product validators consisted of two lecturers from the Biology Study Program, Faculty of Mathematics and Natural Sciences, Tanjungpura University, three biology teachers from 2 high schools in Pontianak City, and one from Sambas Regency. The module validation sheet consists of 4 aspects, namely content, language, presentation, and graphics consisting of 20 indicators. The student response questionnaire consists of three aspects, namely cognitive, affective, and conative aspects, comprising 26 statements. The response questionnaire validators consisted of 2 lecturers from the Biology Education Study Program, FKIP, University of Tanjungpura. Developing a module based on discovery learning sub-material classification of living things is declared feasible because it obtains a validity value of CVR = 1, meaning that the module is valid in content. Modules declared feasible are tested on a limited basis and obtain an average result of 81.9% in the very strong category. Further research is needed to test modules in larger classes.